An Analysis of the MTHFR Gene and Clinical Phenotypes in Familial Non-Syndromic Cleft Palate - Agung Sosiawan, - (Ektodermal Displazi Grubu, 2020)
Non-syndromic Cleft Lip and/or Palate (NSCL/P) Constitutes the most common form of Orofacial Cleft (OFC). The methylene tetra hydrofolate reductase (MTHFR) encoding gene has been reported as playing a vital role in the pathogenesis of NSCL/P. Allele-specific Oligonucleotide (ASO) PCR analysis of A1298C and C677T of MTHFR gene polymorphism was performed using DNA from both the mother and father, in addition to circulating fetal cell -free DNA followed by electrophoresis. Homozygote mutation of A1298C was identified in the circulating fetal cell-free DNA, while heterozygote mutation was found to be present in both parents. Surprisingly, the affected infant possessed normal allele of C677T, despite both parents being heterozygotemutated. Following birth, the infant presented cleft palate defect, even though both parents were phonetically normal. The mutation of both C677T and 1298C genes can cause fusion failure during oral and maxillofacial development. The latter may occur without following typical Mendelian hereditary patterns, despite the fact that NSCL/P is inherited in numerous cases. The irregular hereditary pattern is probably due to an interaction between genetic susceptibility and environmental stimulation.